Governance in Service Delivery in the Middle East and North Africa - University of Gothenburg (World Bank, Washington, DC, 2017)
This paper examines the clientelistic equilibrium that remains prevalent in much of the Middle East and North Africa (MENA) region during the post-independence period, undermining service delivery and creating inequality in access. Political institutions and social practices that shape incentives for policymakers, service providers, and citizens create what can be called a potentially tenuous, “clientelistic equilibrium.” Service delivery is influenced by political institutions that allow for the capture of public jobs and service networks, and by social institutions that call upon individuals to respond more readily to members of their social networks than to others. The result is poor quality service delivery (e.g., absenteeism, insufficient effort), difficulties in access (e.g., need for bribes, connections), and inequalities in the provision of services.